Some efficient implementation schemes for implicit RUNGE-KUTTA methods - Vigneswaran, R.; Kajanthan, S. (Academic Publications, Ltd, 2014)
Several iteration schemes have been proposed to solve the nonlinear equations arising in the implementation of implicit Runge-Kutta methods. As an alternative to the modified Newton scheme, some iteration schemes with reduced linear algebra costs have been proposed A scheme of this type proposed in [9] avoids expensive vector transformations and is computationally more efficient. The rate of convergence of this scheme is examined in [9] when it is applied to the scalar test differential equation x ′ = qx and the convergence rate depends on the spectral radius of the iteration matrix M(z), a function of z = hq, where h is the step-length. In this scheme, we require the spectral radius of M(z) to be zero at z = 0 and at z = ∞ in the z-plane in order to improve the rate of convergence of the scheme. New schemes with parameters are obtained for three-stage and four-stage Gauss methods. Numerical experiments are carried out to confirm the results obtained here.
Keywords: Implementation; Gauss methods; Rate of convergence; Stiff sys- tems